Narrativas da prisão: travestilidade e trajetória de vida em uma prisão LGBT - Alves, Antônia Gabriela de Araújo (2019)
The narratives of transvestites and transsexuals in prison context are the subject of investigation throughout this research that presents as main problem the following question: “How are the experiences of transvestites and transsexuals perceived in a LGBT + prison unit?” The research context is a “ LGBT prison ”, a category prepared by inmates, located in the city of Itaitinga in the state of Ceará. The research is located in the field of anthropology, the ethnographic encounter is represented from the sensory aspects to the repercussion, in the form of affectation and writing of the researcher. The meeting is narrated, but also the strangeness, the foreignness of a researcher in prison. The descriptive densification of this relationship with space and the interlocutors build new meanings for anthropological work. A narrative is a process of fabulation and memory in action, that is, being spoken has the function of creating meanings. Thus, it is clear that life trajectories emulate experiences of confrontation and resistance to state violence in the prison, as well as social violence. The stories of modern prisons, their plurality must be emphasized, are marked by issues of gender, sexuality, race and class, and these categories are useful for the analysis of prison structure as a control mechanism. The birth of a “LGBT prison” creates new routines and needs, emerges as a milestone that alters and reverberates in the trajectory of social movements and respect for human rights. However, it should be noted that the existence of this space does not guarantee full respect and access to the dignity of transvestites and transsexuals. These problematizations are brought about by the life trajectories of trapped transvestites, the activism conceived by an imprisoned transvestite, the intersectionality of prison experiences, the plot of “unspeakable freedoms”, the production of narratives under the surface of fanzines and existences that represent resistance.